“Stop crying your heart out”: how failed founders can use emotional failure narratives - Patrick Spieth; Christian D. Klusmann; Sascha Klein (Review of Managerial Science, 2023)
Failed founders experience very intense emotions resulting from their entrepreneurial failure. Since many founders are not discouraged by failure and consider founding a subsequent startup, the need to deal with the stigma attached to failed founders. Applying an experimental research design, this study investigates how failed founders can use emotional failure narratives to approach potential co-founders for their subsequent venture project. We demonstrate that the use of failure narratives that contain both negative and positive emotions lead to higher perceived attractiveness of a failed founder's new startup attempt among potential co-founders than either purely negative or positive emotional failure narratives.
Keywords: 650; Emotion as social information theory; Entrepreneurial emotions; Entrepreneurial failure; Failure narratives